Sensitivity, Specificity, and Diagnosting Value of Bahrudin’s Score in Diagnosing Stroke Compared to CT-Scan - Mochamad Bahrudin; Salsabilla Rihadatul Aisy (Saintika Medika, 2020)
Stroke is an emergency situation leading to disability and death. Fast, precise, and easy diagnostic tools is needed as an substitute for CT-Scan, especially when CT-Scan is not available. This study is conducted to determined sensitivity, specificity, and diagnostic value of Bahrudin’s Score compared to CT-Scan in diagnosing bleeding or infarct stroke. This research was conducted at Gambiran Kediri Hospital and Lamongan Muhammadiyah Hospital using 89 patients as samples. It was analyzed to define sensitivity, specificity, positive predictive value, negative predictive value,  positive likelihood ratio, negative likelihood ratio, accuracy, reciever operating characteristic curve, and area under curve in order to define diagnostic value of Bahrudin’s Score. Infarct stroke was found in 54%, 58% happened in male and 96,6% found in age over 40.   Sensitivity of Bahrudin’s Score is 0.868, specificity 0.860, positive predictive value os 0.825, negative predictive value is 0.896, positive likelihood ratio is 6.600, negative likelihood ratio is 0.153, accuracy 0.864, and AUC 86.4%. It is determined that Bahrudin’s score with AUC 86.4% is feasible to replace CT-Scan when it is not available.